2017
DOI: 10.1007/s10067-017-3916-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk of active tuberculosis in patients with inflammatory arthritis receiving TNF inhibitors: a look beyond the baseline tuberculosis screening protocol

Abstract: Tuberculosis (TB) is a major concern in patients receiving TNF inhibitors (TNFi). This study aimed to assess the incidence of active TB and the efficacy of TB prevention measures used over the years, and to determine risk factors for developing TB, in a single-centre cohort of patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA) and ankylosing spondylitis (AS) receiving TNFi. Data of all patients in whom treatment with TNFi was initiated in our rheumatology clinic until December 1st 2014 have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…The analysis of the risk factors for incident TB revealed that known re-exposure is the most critical cause of this complication. It occurred in a median period of 2 years, and we confirmed the previous observation that new TB infections mostly present as a pulmonary disease ( 18 , 33 , 34 ). In contrast, TB reactivation was observed in approximately one-third of the patients with TB, and the majority of cases were extra-pulmonary with a median of 5.3 months of exposure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The analysis of the risk factors for incident TB revealed that known re-exposure is the most critical cause of this complication. It occurred in a median period of 2 years, and we confirmed the previous observation that new TB infections mostly present as a pulmonary disease ( 18 , 33 , 34 ). In contrast, TB reactivation was observed in approximately one-third of the patients with TB, and the majority of cases were extra-pulmonary with a median of 5.3 months of exposure.…”
Section: Discussionsupporting
confidence: 90%
“…A long-term follow-up was also essential for this evaluation, as TB re-exposure is considered after at least 12 months ( 17 , 18 ), and it has already been shown that the risk remains throughout the treatment ( 19 ). The lack of information regarding the treatment duration ( 3 , 16 , 20 ) precludes an accurate evaluation of the importance of re-exposure in the context of incident TB.…”
Section: Discussionmentioning
confidence: 99%
“…Reactivation of latent tuberculosis infection (LTBI) during TNFi treatment was first reported in 2001 and is now well documented [7–9]. This risk can be reduced by routine screening and treatment of LTBI at the start of immunosuppressive treatment [9, 10]. The national Finnish guidelines for screening and treating LTBI in RA patients were published in 2004 [11].…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α antagonists therapy changed a great percentage of indeterminate results of QTF-GT to positive [15]. Ramos [19].…”
Section: Systematic Review Findingsmentioning
confidence: 99%
“…Active TB has not occurred in patients with positive LTBI. Two subjects with active TB were observed in patients with negative results of TST and QFT-GT The study suggested that LTBI screening and a prophylactic treatment support the safety of biological therapy[18] Soare et al, (2018). assessed the efficacy of TST and QFT-GT for predicting active TB in RA, PsA and AS receiving TNF-α blocker therapy.…”
mentioning
confidence: 99%